KAJIAN PEMANFAATAN AIR ASAM TAMBANG UNTUK MENGAIRI AREAL PERSAWAHAN DI WILAYAH KECAMATAN KINTAP, KABUPATEN TANAH LAUT, PROVINSI KALIMANTAN SELATAN - Jarwanto, Jarwanto Jarwanto (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2021)
Coal mining activities that open land can cause various technical problems. Acid mining water formed due to mining activities with an area of 32.8 Ha causes a low pH to almost touch number 4 which is in the mining working pool (sump). The need to handle acid mine drainage in order to comply with quality standards. In addition, water from mining can be used by the local community. The construction of the sediment pond is placed 30 meters above the mining work area, by pumping it using a 6